Vatican I's Teaching on Papal Infallibility: Nineteenth-Century Historical Context and Twenty-First-Century Relevance. Issue 1 (June 2020) - von Arx, Jeffrey
Abstract : How has Pastor Aeternus stood the test of time in the face of Vatican II, the great social leveling brought about by democracy and the mass media, and the severe erosion of confidence in hierarchical institutions, including the Catholic Church?